Design and experiment of vibration plate type camellia fruit picking machine - Wu, Delin; Ding, Da; Cui, Bowen; Jiang, Shan; Zhao, Enlong; Liu, Yangyang; Cao, Chengmao (International Journal of Agricultural and Biological Engineering, 2022)
In order to solve the problem of high missed rate of camellia fruits and high damage rate of flower buds during vibratory picking, through the study on the biological characteristics of camellia tree, the crown of camellia tree was divided into upper and lower canopy at the maximum canopy diameter. A kind of vibration plate type camellia fruit picking machine was designed. The structure and working principle of the whole machine were described. Through the analysis of the factors of camellia fruit abscission, it is concluded that frequency, amplitude and working time are the main factors affecting the magnitude of inertia force. Through preliminary research and coupling simulation, the horizontal range of each factor is determined: operation time is 5 s, 10 s, 15 s, frequency is 3 Hz, 5 Hz, 7 Hz and amplitude is 50 mm, 60 mm, 70 mm. Orthogonal tests were carried out on the upper and lower canopies successively, and the comprehensive scoring method was used to analyze the orthogonal test results. The results showed that the optimal combination of working parameters for picking camellia in the upper canopy was A3B3C2, that is, the operation time was 15 s, the amplitude was 70 mm and the frequency was 5 Hz. Under this condition, the missed picking rate of camellia fruits was 8.21% and the rate of flower buds damage was 9.12%. The optimal combination of working parameters for picking camellia fruits in the lower canopy was A3B1C3, that is, the operation time was 15 s, the amplitude was 50 mm and the frequency was 7 Hz. Under this condition, the rate of missing picking of camellia fruits was 6.84% and the rate of flower buds damage was 6.92%. Keywords: canopy stratification, structural design, analysis of shedding factors, coupling simulation, orthogonal test DOI: 10.25165/j.ijabe.20221504.6971 Citation: Wu D L, Ding D, Cui B W, Jiang S, Zhao E L, Liu Y Y, et al. Design and experiment of vibration plate type camellia fruit picking machine. Int J Agric & Biol Eng, 2022; 15(4): 130–138.